0.5 V fifth-order butterworth low-pass filter using multiple-input OTA for ECG applications - Kumngern, Montree; Aupithak, Nattharinee; Khateb, Fabian; Kulej, Tomasz (My University, 2020)
This paper presents a 0.5 V fifth-order Butterworth low-pass filter based on multiple-input operational transconductance amplifiers (OTA). The filter is designed for electrocardiogram (ECG) acquisition systems and operates in the subthreshold region with nano-watt power consumption. The used multiple-input technique simplifies the overall structure of the OTA and reduces the number of active elements needed to realize the filter. The filter was designed and simulated in the Cadence environment using a 0.18 µm Complementary Metal Oxide Semiconductor (CMOS) process from Taiwan Semiconductor Manufacturing Company (TSMC). Simulation results show that the filter has a bandwidth of 250 Hz, a power consumption of 34.65 nW, a dynamic range of 63.24 dB, attaining a figure-of-merit of 0.0191 pJ. The corner (process, voltage, temperature: PVT) and Monte Carlo (MC) analyses are included to prove the robustness of the filter.
Keywords: Fifth-order low-pass filter; Multiple-input bulk-driven technique; Nanopower; Operational transconductance amplifier; Subthreshold region